Concomitant Atrial Fibrillation Procedures During Cardiac Surgery in a UK Center: Reflection of Worldwide Practice? - Mistirian, Alina-Adriana; Yates, Martin T.; Awad, Wael I. (Frontiers in Cardiovascular Medicine, 2022)
Background: Guidelines recommend concomitant atrial fibrillation (AF) ablation during cardiac surgery to restore normal sinus rhythm (NSR). The study determines, to what extent patients with AF undergoing cardiac surgery at our institution received a concomitant AF procedure, what these procedures entailed, and short-term outcomes. Methods: A retrospective study of 2984 patients undergoing cardiac surgery over 18 months. Patients who were in preoperative AF were identified and those who underwent a concomitant AF procedure (Group 1) were compared with those who did not (Group 2). Results: 313 (10.5%) patients had pre-operative AF; paroxysmal (19.5%), persistent (11.8%), longstanding (63%), unknown (5.8%). 116/313 (37.1%) patients had a concomitant AF procedure: 7.7% patients had a concomitant AF ablation and 29.4% had only a Left Atrial Appendage Occlusion (LAAO). Fewer patients with paroxysmal and persistent AF underwent concomitant AF procedures compared with the ones who had no AF procedures (6.7% vs 12.8% and 17.6% vs 31%, respectively). Greater in-hospital survival (99.1% vs 93.9%, p= 0.025) and survival at a mean follow up of 6 weeks (97.4% vs 89.3%, p= 0.09) was probably determined by patient’s preoperative comorbidities. There were no differences in readmission rates, permanent pacemaker insertion, cerebral events or NSR at discharge or follow-up, between groups. Conclusions: In our center, concomitant AF ablation is performed only in 7.7% of cases, 29.4% had only an LAAO performed at the time of surgery. There was no difference in restoring NSR, cerebral events, or readmission rates compared with patients who had nothing done for their preoperative AF.